Peer tutoring in rehabilitation sciences curriculums: a scoping review - Alison Bell; Chelsea Fagan; Laura Krisa; Rebecca Sinko; Heather Morey (Springer, 2023)
Abstract Background Peer tutoring is a learning strategy where students take on the role of teacher. There are many reported benefits of this model however it is not well described in rehabilitation science curriculums. The aim of this review is to describe the scope of available literature for rehabilitation science education. Methods A systematic scoping review using PubMed, CINAHL, Scopus, and ERIC databases. Inclusion criteria included the English language, peer-reviewed articles that report outcomes of a peer-tutoring program for students enrolled in occupational therapy, physical therapy, speech therapy and or athletic training programs. Consensus between two authors was used for article inclusion and data extraction. Results Sixteen articles were included in the review. Peer tutoring was described in athletic training, occupational therapy, physical therapy, and speech language pathology programs. Peer tutors were students further along in their training in 75% of the included studies. The most common content taught was anatomy (38%) followed by clinical assessment (19%). Just under half (44%) of the included studies incorporated interprofessional education with tutors and tutees representing different fields of study. Outcomes of peer tutoring programs were most commonly assessed with surveys (75%) developed by the research team with only 38% reporting objective measures of learning by the participants. Conclusion Results of this review demonstrate that peer tutoring is used in rehabilitation science curriculums, however, there are a limited number of reports. The learning strategy is well described in other health science education models with many potential benefits. This review can be used to inform the development and evaluation of future peer tutoring programs in rehabilitation sciences curriculums.